A simple two-stage carrier-phase estimation algorithm for 32-QAM coherent optical communication systems - Peng, Min; Wang, Xiangqing; Yang, Xiaokun; Wang, Dongfei (Frontiers in Physics, 2024)
The combination of high-order modulation formats and linewidth-tolerant carrier phase estimation (CPE) can effectively improve spectrum efficiency and relax the limitation of laser linewidth. This paper presents a simple two-stage CPE algorithm for polarization-multiplexed (PM) 32-quadrature amplitude modulation (32-QAM) coherent optical communication systems. The algorithm uses an enhanced QPSK partitioning algorithm combined with a simplified 4th power CPE method for coarse estimation in the initial stage and maximum likelihood (ML) detection in the subsequent fine stage. The CPE algorithm significantly increases the number of symbols used in the first stage of coarse estimation. This results in a significant increase in the stability and reliability of the phase estimation, and the CPE algorithm significantly reduces the computational complexity. The optimal parameters, phase estimation performance, and system performance of the algorithm were investigated by building a 22 Gbaud PM 32-QAM coherent system simulation platform and a 5 Gbaud PM 32-QAM coherent system experimental platform. The results show that the proposed two-stage CPE algorithm has a stronger linewidth tolerance difference than the conventional QPSK, and the two-stage CPE algorithm with an optimal block length of 105 performs comparable to blind phase search (BPS). The optical signal noise Ratio (OSNR) value is 21.2 dB and the bit error rate (BER) is 1.8 × 10 -3 for the optimal block length of 105. The receiving-end DSP unit with a flexible scheme and good communication performance will have potential applications in adaptive elastic optical networks.